Adherence to antiretroviral therapy and viral suppression: Analysis of three periods between 2011 and 2017 at an HIV-AIDS center, Brazil - Milward de Azevedo Meiners, Micheline Marie; Araújo Cruz, Igor; de Toledo, Maria Inês (Frontiers in Pharmacology, 2023)
The increased effectiveness of antiretroviral therapy (ART) in the last 30 years is a scientific landmark, and viral suppression is directly associated with treatment adherence. The aim of this study was to compare the results of ART adherence and viral load suppression with the evolution of the protocols and other associated factors, in people living with HIV. A panel analysis of three descriptive longitudinal studies investigating ART adherence and viral load suppression was conducted in people with HIV treated at a drug dispensing unit in the Federal District. The studies were carried out during periods of 2011, 2013 and 2017, coinciding with the three different recommended treatment schemes for the country. Adherence was assessed using drug dispensing records. Viral load data were obtained from the Ministry of Health´s Laboratory Examination Information System. Analysis of the data of 522 individuals in the three periods showed sociodemographic differences such as a decline in the percentage of women (from 33% in period 1 to 4% in period 3) and an increase in the percentage of young people. ART adherence was higher in period 2 (tenofovir/lamivudine/efavirenz scheme). Viral load suppression was greater in period 3 (tenofovir/lamivudine/dolutegravir scheme). The relative detectable viral load risk was nearly two-fold higher (RR 1.83) in people living with HIV with less than 80% adherence when compared to those above 80%. With respect to the different schemes recommended in Brazil during the periods studied, ART containing dolutegravir was the most effective in achieving viral load suppression. By contrast, there was better ART adherence in the daily combined fixed dose consisting of tenofovir/lamivudine/efavirenz in tablet form. Adherence to ART above 80% seemed to be enough to promote an effective treatment in therapeutic schemes including efavirenz or dolutegravir.